Audio-visual experience strengthens multisensory assemblies in adult mouse visual cortex - Thomas Knöpfel (Nature Portfolio, 2019)
Sensory stimuli usually arrive simultaneously but the neural-circuit mechanisms that combine multiple streams of sensory information are incompletely understood. The authors here show that visual-auditory pairing drives plasticity in multi-modal neuron networks within the mouse visual cortex.